Pengaruh Locus Of Control dan Need For Achievement Terhadap Intensi Berwirausaha Pada Siswa MAN 1 Kota Payakumbuh - Fatika, Cindy; Rahmidani, Rose (Jurnal Salingka Nagari, 2022)
The goal of this study is to determine the effect of locus of control and the need for achievement on the entrepreneurial intentions of MAN 1 Payakumbuh students. The causative form was used in this study, and the population consisted of MAN 1 Payakumbuh students. The survey sample consists of 260 respondents who were chosen using a proportional random sampling technique. This study relied on primary data gathered through the distribution of questionnaires to selected MAN 1 Payakumbuh students. SPSS 20 path analysis was used as the analysis method. The findings of this study indicate that the locus of control and the need for achievement have a significant impact on entrepreneurial intentions. The locus of control influences entrepreneurial intentions significantly. The need for achievement has a significant impact on entrepreneurial intentions.